The Influence of Training, Motivation, Discipline, Work Life Balance on Performance in SMK Duta Karya - Muhammad Alvin Jauhari; Popong Nurhayati; Yunus Triyonggo (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: SMK Duta Karya Kudus has received support from the local government through the Vocational School Development Program based on the Industrial Revolution 4.0 to improve the quality of human resources. Despite this, an internal survey indicates that the performance of teachers and administrative staff remains below expectations.Purpose: This study aims to analyze the influence of training, motivation, discipline, and work-life- balance on human resource performance at SMK Duta Karya Kudus and to propose strategic recommendations for performance improvement.Design/methodology/approach: This research employs descriptive statistical analysis and Structural Equation Modeling-Partial Least Squares (SEM-PLS) to examine the relationships among variables. The analysis is based on data collected from the school environment to ensure contextual relevance and practical applicability.Findings/Result: The findings reveal that motivation and work life balance significantly affect human resource performance. Motivation has the highest impact, with a path coefficient of 0.462 and a p-value of 0.000 (p < 0.05), followed by work life balance with an original sample value of 0.369 and a p-value of 0.000 (p < 0.05). Based on these findings, two strategic recommendations are proposed: (1) providing monthly financial incentives to outstanding teachers and administrative staff, and (2) implementing flexible learning models through platforms such as Zoom to support remote teaching and administrative tasks.Conclusion: The study concludes that motivation and work-life-balance are critical factors in enhancing human resource performance in vocational schools. Strategic interventions focusing on these aspects are necessary to align HR performance with the goals of the Industrial Revolution 4.0 framework.Originality/value (State of the art): This study contributes to the limited empirical literature on HR performance improvement in vocational education settings aligned with Industry 4.0 demands. By integrating SEM-PLS analysis with practical strategy formulation, it offers actionable insights for educational institutions seeking to optimize staff performance in the digital era. Keywords: human resource, industrial revolution, motivation, SEM-PLS, work life balance